Brand Ambassador, Social Media Marketing, and Product Innovation Effects on Purchase Decisions: The Mediating Role of Brand Image in the Indonesian Dairy Industry - Wardani, Naili Rohmah Kusuma; Fachrunnisa, Olivia (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
This study aims to comprehensively analyze the influence of Brand Ambassador, Social Media Marketing, and Product Innovation on Purchase Decision, with Brand Image positioned as a mediating variable. In an increasingly competitive market, companies must implement effective marketing strategies that not only attract consumer attention but also strengthen brand perception and drive actual purchasing behavior. Brand ambassadors are expected to enhance credibility and emotional attachment, while social media marketing plays a strategic role in delivering interactive and persuasive promotional content. Meanwhile, product innovation helps maintain relevance and competitive advantage in the marketplace. This research adopts a quantitative explanatory approach to examine the causal relationships among variables. Data were collected through structured questionnaires distributed to 250 consumers aged 18–40 years who are familiar with the brand ambassador representing the product. The sample was selected to represent active consumers who are frequently exposed to digital marketing. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), which is suitable for assessing complex models involving mediation effects. The findings indicate that Brand Ambassador, Social Media Marketing, and Product Innovation have a significant positive effect on Purchase Decision. Furthermore, the results confirm that Brand Image plays a mediating role, strengthening both the direct and indirect relationships between the independent variables and Purchase Decision. These findings suggest that an integrated marketing strategy focusing on credible ambassadors, engaging digital promotion, and continuous innovation can effectively enhance brand image and ultimately drive consumer purchasing decisions.